Relationship between serum adipokine levels and radiographic progression in patients with ankylosing spondylitis: A preliminary 2-year longitudinal study - Park, Ji-Heh; Lee, Seung-Geun; Jeon, Yun-Kyung; Park, Eun-Kyoung; Suh, Young-Sun; Kim, Hyun-Ok (Medicine (Baltimore), 2017)
The immunomodulatory effects of adipokines have been extensively studied in rheumatic diseases, and there is a paucity of information regarding their effects on bone metabolism.The aim of this study was to investigate the relationships between serum adipokines levels and radiographic progression over 2 years in patients with ankylosing spondylitis (AS).In this preliminary longitudinal study, we prospectively recruited 20 consecutive male patients with AS and 11 gender- and age-matched healthy subjects. At the baseline and 2-year follow-up, serum adiponectin, leptin, resistin, tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6, and Dickkopf-1(DKK-1) levels were measured in AS patients using enzyme-linked immunosorbent assays; these measurements were only performed at the baseline for healthy controls. Radiographic progression was determined as the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) progression of ≥2 by comparing the baseline and 2-year follow-up radiographs.All AS patients were naive to TNF-α blockers at the enrollment and during the 2-year follow-up period and their median disease duration was 51.5 months. At the baseline, the serum resistin, TNF-α, and IL-6 levels were significantly higher in AS patients than in controls. At the 2-year follow-up, the median mSASSS of AS patients was found to be significantly increased from the baseline (8-10.5, P = .001) and 7 (35%) AS patients showed radiographic progression. In AS patients, the leptin and resistin levels were significantly higher at the 2-year follow-up than at the baseline. The baseline resistin levels and changes in leptin levels from the baseline to the 2-year follow-up were significantly higher in AS patients with radiographic progression than in those without radiographic progression (P = .002 and .024, respectively). The baseline resistin levels and the increase in leptin levels during the follow-up period significantly correlated with changes in mSASSS (ρ = 0.528 and 0.559, P = .017 and .01, respectively). No association between changes in serum adipokine levels and disease activity in AS patients was observed.Our findings suggest that leptin and resistin may contribute to the pathogenesis of new bone formation rather than to inflammatory processes and have the potential to be used as biomarkers of the structural outcome of AS.